(1−x)Bi0.5Na0.5TiO3−xK0.5Na0.5NbO3 ceramics with low coercive field: Preparation from hydrothermally synthesized precursor powders. Issue 1 (January 2015) - Li, Shite; Chen, Liangping; Ning, Xiaojie; Guo, Min; Zhang, Mei
Abstract: In the paper, (1− x )Bi0.5 Na0.5 TiO3 − x K0.5 Na0.5 NbO3 ((1− x )BNT− x KNN, (0≤ x ≤0.08) powders with perovskite structure were firstly synthesized by the hydrothermal method, then the highly dense piezoelectric ceramics exhibiting lower coercive field were prepared by sintering (1− x )BNT− x KNN powders at 1150 °C for 2 h, followed by polarizing it in silicon oil at 80 °C for 5 min. The phase compositions and micro-morphology of (1− x )BNT− x KNN powders and ceramics were characterized by X-ray diffraction and field emission scanning electron microscope. The results showed that (1− x )BNT– x KNN (0≤ x ≤0.09) powders and ceramics dispersibility and crystal morphology could be successfully synthesized at 210 °C for 24 h by the hydrothermal method with KOH/NaOH=1:7 (molar ratio) in precursor when Ti(OC4 H9 )4 was used as titanium source. With the addition of KNN, the grain size of prepared powders became smaller and more disperse. The crystal structure of (1− x )BNT– x KNN ceramics was found to be changed from rhombohedral to pseudo-cubic phase combined with morphology change from regular round shape to cubic or rectangular shape. When the actual KNN content was in the range of 0.04–0.05, abrupt changes in both the phase and morphology of the ceramics were observed. This would be indicative of the formation of a rhombohedral and pseudo-cubic morphtropic phase boundary (MPB). The piezoelectric constant d33 gradually reached its highest value of 96 pC/N at x =0.04, with the coercive field Ec of ceramics as 28 KV/cm. This result was much lower than that of pure BNT (45 KV/cm), indicating that the doping of KNN successfully decreases coercive field Ec of BNT ceramics.